2023
DOI: 10.17977/um005v7i12023p44
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Culture, Policy, and Practice Index on the Quality of Inclusive School Education in South Kalimantan

Abstract: This study aims to measure the effect of the index of policy, culture, and teaching practice on the quality of inclusive education in South Kalimantan. This study uses a quantitative approach with a survey method. The population in this study were Special Education Teachers, Classroom Teachers, Staff, Principals, and Parents providing inclusive education in South Kalimantan. The sampling technique used non-probability sampling with incidental sampling using the Slovin formula. Primary data was obtained by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Implementing inclusive education services comes from various aspects, namely facilities and infrastructure, students with special needs, special guidance teachers, classroom teachers, parents, curriculum, and costs (Amka & Kusumastuti, 2019). In another case, the educational facilities and infrastructure are important resources supporting the schools' learning process (wulan & Sanjaya, 2022).…”
Section: Discussion(s)mentioning
confidence: 99%
“…Implementing inclusive education services comes from various aspects, namely facilities and infrastructure, students with special needs, special guidance teachers, classroom teachers, parents, curriculum, and costs (Amka & Kusumastuti, 2019). In another case, the educational facilities and infrastructure are important resources supporting the schools' learning process (wulan & Sanjaya, 2022).…”
Section: Discussion(s)mentioning
confidence: 99%
“…UNESCO explicitly states that inclusive education is a child's right, not a privilege given to children with special needs. Inclusive education promotes quality and equity in education for all, including those who are potentially marginalized by special learning needs or social position (Junaidi et al, 2022;Ediyanto et al, 2023, Amka et al, 2023Wulan & Sanjaya, 2022). Based on this statement, awareness for equality rises about the rights of children with disabilities to have access to the same educational services as normal children (UNESCO, 2021;Kartini & Aprilia, 2022;Iswari et al, 2023;Ediyanto & Kawai, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusive education has a lot of meanings. The simplest way to define inclusive education is that it gives the equal opportunity for every one to access quality education (Ainscow, 2020;Junaidi et al, 2022;Ediyanto et al, 2023, Amka et al, 2023Wulan & Sanjaya, 2022;Kartini & Aprilia, 2022;Iswari et al, 2023;Ediyanto & Kawai, 2023). Previous studies have given the slight overview on this topic, and reported that some challenges are still exist, and the quality inclusive education is still far from reach (Fedulova et al, 2019;Wang, 2019).…”
Section: Introductionmentioning
confidence: 99%